Tolerance in Maize Landraces to Diabrotica speciosa (Coleoptera: Chrysomelidae) Larvae and Its Relationship to Plant Pigments, Compatible Osmolytes, and Vigor - Costa, Eduardo Neves [UNESP]; Sardinha de Souza, Bruno Henrique [UNESP]; Ribeiro, Zulene Antonio [UNESP]; Mathias dos Santos, Durvalina Maria [UNESP]; Boica Junior, Arlindo Leal [UNESP] (Oxford Univ Press Inc, 2021)
The rootworm Diabrotica speciosa (Germar) is native to South America and causes severe economic losses to several crops due to root feeding and disease spread. In maize (Zea mays L.), losses in production come from larval rootworm attack on plant roots resulting in plant health problems, including stalk lodging. More options for controlling this pest are needed to create well balanced, integrated pest management programs for farmers in this region. Natural sources of tolerance in maize genotypes are important for maize breeding programs, and this study investigated the expression of tolerance in several Brazilian maize landraces to D. speciosa. Plant vigor and compounds associated with plant health, including chlorophylls, carotenoids, glycine betaine, and proline were assessed for each landrace. Five landraces and one maize cultivar were selected based on their levels of antibiosis-resistance to D. speciosa that were determined in a prior screening. The percent reduction in plant growth was used as the measure of tolerance. The landrace Azteca was classified as tolerant to D. speciosa larval feeding, displaying less reduction in plant matter despite having lower plant vigor. This landrace also had higher amounts of chlorophyl and carotenoid pigments, suggesting a positive correlation between tolerance to D. speciosa and higher contents of these photosynthetic pigments. The compatible osmolytes glycine betaine and proline do not seem to be associated with tolerance in maize landraces to D. speciosa larvae. Landrace Azteca seems promising for plant breeding, and repeated field studies are needed to confirm its suitability in maize integrated pest management.
Keywords: Zea mays L; native resistance; chlorophyl; carotenoids; glycine betaine